Employee Rhetorical Sensitivity as a Mediator in the Relationship Between Customer Orientation and Customer Retention - Mokhtaruddin, Suraya Akmar; Wel, Che Aniza Che; Khalid, Nor Rahimy (UI Scholars Hub, 2019)
Research Aims: The current study proposes to fill in the gap in customer orientation literature by focusing on the relationship between customer orientation, employee rhetorical sensitivity and customer retention from the customer perspective. Design/methodology/approach: The questionnaires were distributed at the KLIA and KLIA2 among experienced customer of travel agency, where the respondents were selected using convenience sampling. Research Findings: The finding indicates that customer orientation and employee rhetorical sensitivity has positively influence customer retention. Additionally, employee rhetorical sensitivity partially mediates the relationship between customer orientation and customer retention. Theoretical Contribution/Originality: Academically, this study contributes to the literature of customer orientation and rhetorical sensitivity. Managerial Implication in the South East Asian context: Practically, it will lead to better understanding of customer orientation as well as employee rhetorical sensitivity in enhancing travel agency’s services in Malaysia and South East Asian Country. Research limitation & implications: This study only focuses on customer orientation and employee rhetorical sensitivity as a predictor of customer orientation. It also employs a cross-sectional research design, which only measures the phenomenon once.